Actinomycins inhibit the production of the siderophore pyoverdines in the plant pathogen Pseudomonas cichorii SPC9018. Issue 10 (2nd October 2020) - Maenaka, Risa; Tani, Shuji; Hikichi, Yasufumi; Kai, Kenji
ABSTRACT: Pyoverdines, a group of peptide siderophores produced by Pseudomonas species, function not only in iron acquisition, but also in their virulence in hosts. Thus, chemical inhibition of pyoverdine production may be an effective strategy to control Pseudomonas virulence. In the plant pathogen Pseudomonas cichorii SPC9018 (SPC9018), pyoverdine production is required for virulence on eggplant. We screened microbial culture extracts in a pyoverdine-production inhibition assay of SPC9018 and found Streptomyces sp. RM-32 as a candidate-producer. We isolated two active compounds from RM-32 cultures, and elucidated their structures to be actinomycins X2 and D. Actinomycins X2 and D inhibited pyoverdine production by SPC9018 with IC50 values of 17.6 and 29.6 μM, respectively. Furthermore, pyoverdine production in other Pseudomonas bacteria, such as the mushroom pathogen P. tolaasii, was inhibited by the actinomycins. Therefore, these actinomycins may be useful as chemical tools to examine pyoverdine functions and as seed compounds for anti- Pseudomonas virulence agents. Abstract : uf0001 Actinomycins may be useful as chemical tools to examine pyoverdine functions and as seed compounds for anti- Pseudomonas virulence agents.